Bioremediation of Petroleum Hydrocarbons in the Upper Parts of Sandy Beaches - Abou-Khalil, Charbel; Prince, Roger C.; Greer, Charles W.; Lee, Kenneth; Boufadel, Michel C. (Environmental science & technology, 2022)
The biodegradation of dispersed crude oil in the ocean is relatively rapid (a half-life of a few weeks). However, it is often much slower on shorelines, usually attributed to low moisture content, nutrient limitation, and higher oil concentrations in beaches than in dispersed plumes. Another factor may be the increased salinity of the upper intertidal and supratidal zones because these parts of the beach are potentially subject to prolonged evaporation and only intermittent inundation. We have investigated whether such an increase in salinity has inhibitory effects on oil biodegradation in seashores. Lightly weathered Hibernia crude oil was added to beach sand at 1 or 10 mL/kg, and fresh seawater, at salinities of 30, 90, and 160 g/L, was added to 20% saturation. The biodegradation of oil was slower at higher salinities, where the half-life increased from 40 days at 30 g/L salts to 58 and 76 days at 90 and 160 g/L salts, respectively, and adding fertilizers somewhat enhanced oil biodegradation. Increased oil concentration in the sand, from 1 to 10 mL/kg, slowed the half-life by about 10-fold. Consequently, occasional irrigation with fertilization could be a suitable bioremediation strategy for the upper parts of contaminated beaches. However, dispersing oil at sea is probably the most suitable option for the optimal removal of spilled crude oil from the marine environment.